Vers un « Runet souverain » ? Perspectives et limites de la stratégie russe de contrôle de l’Internet - Kevin Limonier (EchoGéo)
In 2019, the State Duma approved a law designed to give the authorities the legal and technical means to control data flows in and out of Russian territory, and to disconnect the national network from the rest of the world "in case of threat." This "Sovereign Runet" law can be considered as the culmination of Russia's digital sovereignty strategy since the beginning of the 2010s. However, its application faces significant difficulties, which this article aims to highlight through spatial analysis and cartography. Using large volumes of data, this work sketches a first map of the Russian Internet routes and actors, in order to point out the challenges the "Sovereign Runet" is now facing.